2016
DOI: 10.1007/s13277-016-5094-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-125b promotes invasion and metastasis of gastric cancer by targeting STARD13 and NEU1

Abstract: MicroRNAs have been documented playing key roles in cancer development and progression. Here, we investigate the role of miR-125b in gastric cancer metastasis. We found that the expression of miR-125b was up-regulated in gastric cancer tissue specimens compared with their corresponding nontumorous tissues, and the up-regulated miR-125b level was significantly associated with TNM stage and lymph node-metastasis. Overexpression of miR-125b promoted gastric cancer cell migration and invasion in vitro and metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…The particular role of microRNA’s, however, seems to be complex and depending on the tumor entity. For example, miR-125b has been shown to be upregulated in tissue of gastric cancer and to enhance spread of gastric cancer metastases43, but to inhibit formation of metastases in hepatocellular carcinoma44. We did not aim to assess a potential relation between ascites microRNA and malignancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The particular role of microRNA’s, however, seems to be complex and depending on the tumor entity. For example, miR-125b has been shown to be upregulated in tissue of gastric cancer and to enhance spread of gastric cancer metastases43, but to inhibit formation of metastases in hepatocellular carcinoma44. We did not aim to assess a potential relation between ascites microRNA and malignancy in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Various targets of miR‐125b, including STARD13, HK2, NEU1, TNFAIP3, and NKIRAS, have been recognized and confirmed in many studies. In our previous study, STAT3 was identified as the direct target of miR‐125b .…”
Section: Discussionmentioning
confidence: 87%
“…Kato et al (69) has reported that NEU1 overexpression resulted in suppression of lung metastasis in melanoma. In addition, suppression of NEU1 by miR-125b has been shown to promote migration, invasion and metastasis in gastric cancers (70). However, NEU1 can also have pro-metastatic effects in pancreatic and ovarian cancers (71), and thus it is not entirely clear what the overall impact of increased NEU1 levels might be in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%